Pengaruh Trust dan Communication Terhadap Customer Loyalty di Perbankan (Studi Kasus pada nasabah Bank Mandiri Cabang Soekarno Hatta di Malang) - Febrina Mayang Sari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The purpose of the study to determine the variables of trust and communication in partial effect on customer loyalty customer Soekarno Hatta bank branch in Malang, and to determine the trust and communication variables jointly influence on customer loyalty customer Soekarno Hatta bank branch in Malang. The population used in this study is a customer of the bank branch in Malang Soekarno Hatta with the characteristics of men and women, residing in Malang, at least high school education or its equivalent for the reason the customer has the ability to understand the questions on the questionnaire, the minimum has been customer savings bank during the past 2 years. The number of samples used is 130 respondent. The research proves that trust (X1) and Communication (X2) simultaneously significant effect on customer loyalty variables. means higher customer confidence and better communication that exists only between the bank and its customers, the higher will affect customer loyalty to Bank Mandiri. The research proves that trust and communication are partially significant effect on customer loyalty variables. Keywords: Trust, Communication, Customer Loyalty